Molecular Docking and Molecular Dynamic Studies of Semi-Synthetic Piperidine Alkaloids as Acetylcholinesterase Inhibitors - Danuello, Amanda [UNESP]; Romeiro, Nelilma C.; Giesel, Guilherme M.; Pivatto, Marcos [UNESP]; Viegas, Claudio; Verli, Hugo; Barreiro, Eliezer J.; Fraga, Carlos A. M.; Castro, Newton G.; Bolzani, Vanderlan da Silva [UNESP] (Soc Brasileira Quimica, 2012)
The mixture of semi-synthetic derivatives (-)-3-O-acetyl-cassine hydrochloride and (-)-3-O-acetyl-spectaline hydrochloride, prepared from the mixture of natural alkaloids (-)-cassine and (-)-spectaline (4:1) isolated from Senna spectabilis, has been shown to be a potent acetylcholinesterase (AChE) inhibitor, thereby prompting further molecular studies. In this sense, docking and dynamic molecular studies were carried out in this work, aiming to acquire a deeper understanding about all the structural aspects of molecules (-)-3-O-acetyl-cassine and (-)-3-O-acetyl-spectaline hydrochlorides, which differ with respect to their AChE inhibitory potentials. Both molecules establish important interactions with the peripheral anionic site within the catalytic gorge of Torpedo californica AChE. However, only the major compound (-)-3-O-acetyl-cassine hydrochloride significantly interacts with the catalytic triad. Explicit-solvent molecular dynamic simulations were conducted in order to gain better understanding about the hypothetical interactions taking place between the semi-synthetic alkaloid molecules (-)-3-O-acetyl-cassine and (-)-3-O-acetyl-spectaline hydrochlorides and AChE. The data obtained in this study indicated that (-)-3-O-acetyl-cassine hydrochloride is the most potent inhibitor of AChE possibly due to the favorable interactions of this molecule with the target protein, with lower desolvation cost. These results suggested that the size of the side chain has an effect on the inhibitory potential of the evaluated molecules and may represent the starting point for the development of new derivatives of (-)-3-O-acetyl-cassine hydrochloride, with a view to the discovery of new effective AChE inhibitors.
Keywords: molecular docking; molecular dynamic; piperidine alkaloids; acetylcholinesterase inhibitors